2022
DOI: 10.1364/ol.458954
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Wannier–Stark ladder in plasmonic waveguide arrays

Abstract: Evanescently coupled waveguides are a powerful platform to study and visualize the wave dynamics in tight-binding systems. Here, we investigate the propagation of surface plasmon polaritons in arrays of dielectric loaded surface plasmon polariton waveguides with a propagation constant gradient acting as an effective external potential. Using leakage radiation microscopy, we observe in real-space for single site excitation a periodic breathing of the wave packet and an oscillatory motion in the case of Gaussian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In contrast, we have shown that the state shift in a dynamically modulated Wannier-Stark ladder is also strictly quantized during one adiabatic cycle and at the same time, the dispersion of the distribution is bounded by one unit cell. The protocol can be implemented, for example, in arrays of evanescently coupled dielectric waveguides [32]. Finally, it should be mentioned that similar ideas can be applied to many-particle systems to study topological phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we have shown that the state shift in a dynamically modulated Wannier-Stark ladder is also strictly quantized during one adiabatic cycle and at the same time, the dispersion of the distribution is bounded by one unit cell. The protocol can be implemented, for example, in arrays of evanescently coupled dielectric waveguides [32]. Finally, it should be mentioned that similar ideas can be applied to many-particle systems to study topological phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Tight-binding lattice Hamiltonians subject to a constant force parallel to the lattice are called Wannier-Stark ladders [31] and their spectral properties and dynamics has extensively been studied in the past. The Wannier-Stark ladder has recently been implemented in arrays of evanescently coupled dielectric waveguides for surface plasmon-polaritons [32].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review on optical Bloch oscillations, Zener tunneling and related effects can be found in [21]. It is important to acknowledge that Bloch oscillations are a very generic effect and occur in a large number of physical systems such as atomic systems [22][23][24][25][26][27], lasers [28], coupled LC circuits [29], mechanical systems [30][31][32][33], plasmonic [34][35][36][37][38][39] or exciton-polariton systems [40][41][42].…”
Section: Introductionmentioning
confidence: 99%